A method of reducing peak-to-average power ratio (PAPR) - Mohd Ali, Borhanuddin; Varahram, Pooria; Hamidon, Mohd Nizar (2011)
A method of reducing peak-to-average power ratio (PAPR) in orthogonal frequency division multiplex (OFDM) systems is provided, wherein the method includes the steps of generating a matrix of random phase sequence based on interleaved formation, adding of a dummy sequence to an input signal, partitioning the input signal with dummy sequence into sub blocks, multiplying the matrix of interleaved phase sequence with an input signal, performing a search for optimum phase sequence, comparing the minimum PAPR with the threshold and retrieving signal at receiver.